The Oxford handbook of IPOs - Cumming, Douglas; Johan, Sofia A. (New York : Oxford University Press, 2018)
Firms generally begin as privately owned entities. When they grow large enough, the decision to go public and its consequences are among the most crucial times in a firm's life cycle. The first time a firm is a reporting issuer gives rise to tremendous responsibilities about disclosing public information and accountability to a wide array of retail shareholders and institutional investors. Initial public offerings (IPOs) offer tremendous opportunities to raise capital. The economic and legal landscape for IPOs has been rapidly evolving across countries. Financial regulation of analysts and investment banks has been evolving in ways that drastically impact the economics of going public. This Handbook not only systematically and comprehensively consolidates a large body of literature on IPOs, but provides a foundation for future debates and inquiry.
IPO Market Conditions and Timing Over the Long Run / Chris Yung -- Determinants for Variation in IPO Underpricing / Thomas Boulton, Scott Smart, Chad Zutter -- Survey and Synthesis of the IPO Underpricing Literature: The Fixed-Offer Price Constraint as a Unifying Core Explanation / Steven Jones, John C. Yeoman -- The Law and Economics of the Going-Public Decision / Jay B. Kesten -- Auditor Selection and IPO Underpricing / Miriam Koning -- The Structure and Role of the Underwriting Syndicate / Sébastien Dereeper, Armin Schwienbacher -- The Impact of IPOs' Analyst Coverage on the Choice and Timing of SEOs: A Survival Analysis / Nesrine Bouzouita, Carole Gresse -- Survival of Initial Public Offerings on Europe's New Stock Markets / Tao Jiao, Peter Roosenboom, Giancarlo Giudici -- IPOs in a major Emerging Market Economy - India / Rajesh Chakrabarti -- Initial Public Offerings in Germany between 1997 and 2015 / Andreas Oehler, Tim Herberger, Matthias Horn -- IPOs in New Zealand: An Analysis of Benchmark-Adjusted Performance / Huong Dang, Michael Jolly -- Is Exchange Regulation Effective for Junior Public Equity Markets? / J. Ari Pandes, Michael Robinson -- Going Public in China: Reverse Mergers vs IPOs on Chinese Markets / Zijian (Vincent) Cheng, Grant Fleming, Zhangxin (Frank) Liu -- Initial Public Offerings in Hong Kong / Queenie Lai -- IPO Regulators Gone Wild / Kevin K. Boeh, Craig Dunbar -- Venture Capital and Financial Reporting in Newly Public Firms / Lars Helge Hass, Monika Tarsalewska -- The Admission and Regulation of Overseas Issuers: A Survey of Top Four Financial Centers / Horace Yeung -- Lower Visibility Platforms Serving as Stepping Stones to National Stock Exchanges: The Case of Shell Reverse Mergers / Joseph J. Cecala, Jr., Ioannis V. Floros -- SPAC IPOs / Yochanan Shachmurove, Milos Vulanovic -- Crowdfunding: Business and Regulatory Perspective / Alexandra Horváthová -
Statement of responsibility on cover image indicates that Sofia A. Johan is also editor.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 10, 2018).
Keywords: Going public (Securities); Investments